Thalidomide- and bortezomib-induced neuropathy in multiple myeloma, possibility of treatment of neuropathic pain. Recommendations of the Polish Myeloma Study Group - Bilińska, Małgorzata; Usnarska-Zubkiewicz, Lidia; Doboszyńska, Anna (Contemporary Oncology/Współczesna Onkologia, 2008)
The authors on the basis of literature present clinical and electrophysiological data concerning thalidomide and bortezomib-induced neuropathy. Treat-ment-induced peripheral nerve lesion represents dose-dependent sensorimotor length-dependent axonal neuropathy. In some cases the degree of painful paresthesias and numbness result in discontinuation of cytostatic treatment. The pathology of chemotherapy-induced painful neuropathy is not well known yet and presumably differs from pain initiating mechanisms in diabetic painful neuropathy (DPN) as well as postherpetic neuralgia (PHN). The authors suggest that in the situation of limited possibilities for rescuing axons and neurocytes in peripheral nerves from the consequences of toxic chemotherapy, it is indicated to treat neuropathic pain on the basis of experience in other severe pain syndromes. Current pharmacological regimens leading to prevention of neuropathic pain are presented in this paper, including antidepressant and antiepileptic agents, opioids, NMDA receptor antagonists and cannabinoids. The authors postulate introduction of these methods in the treatment of painful, treatment-induced neuropathy in multiple myeloma.